IMPLICATIONS OF WAQF PLEDGES AND LEGAL PROTECTION FOR NADZIR: STUDY NURUL ISLAM MOSQUE IN PUDAKPAYUNG, BANYUMANIK, SEMARANG - Susanto, Hafidz Setyo; Baidhowi, Baidhowi (fakultas hukum universitas PGRI Semarang, 2025)
This study examines the legal status and issues surrounding waqf management in Indonesia, focusing on the case of the Nurul Islam Mosque dispute in Pudakpayung, Banyumanik, Semarang. The purpose of this study is to provide insight to stakeholders who have rights and obligations in waqf, particularly in relation to waqf certificate statements. The research method used is legal empiricism, with a qualitative approach to analyze complex phenomena that encompass normative legal aspects and their implementation in practice. The results from study prove that (1) there are still several fundamental violations in the management of waqf, even though the waqf declaration has been carried accordance with applicable legal procedures, such as: violations purpose of wakaf asset use, failure of nazhir to carry their duties and authorities, and weak supervision from the Indonesian Wakaf Board, and (2) legal protection efforts for nazhir in wakaf management by replacing nazhir who do not carry out their duties, regulating buildings that are not in accordance with their intended use, regulating activities in mosques, and under the supervision of the Indonesian Waqf Board and the Ministry of Religious Affairs.